Development of Electronic Learning Media Book Voice Text Based - Perdana, Oktana Wahyu; Hartanto, Supri; Permana, Septian Aji; Afriyeni, Firli; Nurgiansah, T Heru (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2025)
This study aims to develop Pancasila learning media into an electronic book based on voice text so that it is expected to increase students' learning motivation. The second objective is to determine the feasibility of developing electronic book media based on voice text. The research method uses Research and Development with the stages of Analysis, Design, Development Implementation, and Evaluation (ADDIE). The effectiveness of the media is obtained from the evaluation results of Based on expert validation, electronic book media based on voice text gets an average percentage score of 89% with a very feasible category and the average validation of electronic book material based on voice text gets a score of 92% with a very appropriate category and in terms of user practicality gets a score of 88% with a very appropriate category.